The effect of macroeconomic variables on Islamic Unit Trust fund / Noor Shuaida Abu Bakar - Abu Bakar, Noor Shuaida (Faculty of Business Management, 2014)
This paper is made to find out about the effect macroeconomic variables with Islamic unit trust fund. By using the secondary data for this analysis is retrieved from other journal, article, bank statistic and DataStream. Sample data for this study comprises of 10 companies randomly selected from DataStream on over ten years started from 2004 to 2013. The methodology used for this study is by using the Multiple Linear Regression with panel data sourced from DataStream. In this study, the dependent variable is return of Islamic unit trust fund while the independent are macroeconomic variables. Based on the variables, the purpose of the study is to invstigate the linkage or relationship between the macroeconomic variables on the Islamic unit trust in Malaysia for ten years started from 2004 until 2013. In addition, this research like to explore the effects of macroeconomic variables example gross domestic product (GDP), interest rate (BLR) and inflation rate (CPI) to the return on Islamic unit trust fund. As for this study an individual need to maintain their own portfolio of investment, they need to keep up date with market information and sentiments. Also, in making better judgment whether to buy or sell the funds, as the investors should know what will affect their funds returns in order to get high return in the future. Therefore, it highlights the most important of macroeconomic variables to ensure that improvement in company’s market return. Thus, the result of this research paper will help the company especially the manager and investor to identify the steps that should be taken before make the decision on Islamic unit trust fund.